Penerapan Game Edukasi 3D Endless Runner Berbasis Android Sebagai Media Belajar Matematika Anak - Ghani, Muhamad Abdul; Pohan, Achmad Baroqah; Gunawan, Deni; Saputra, Yoga (Infotek: Jurnal Informatika dan Teknologi, 2024)
In the current pandemic era where learning media is done online, information technology is needed to help online learning media. Video Game is one of the information technology software that is currently developing, there are lots of devices that can be used to play video games such as computers, laptops, smartphones, etc. Since the era of the Video Game era, many genres of games were created, one of which is “Endless Runner”. Due to the lack of interest in mathematics which makes elementary school achievement low in Indonesia, for this reason the author tries to make an Android-based 3D Educational Game “Endless Runner” using the Unity3D application with the C # language program and researched using GDLC for learning mathematics  cause the genre of this game is suitable for children, where there is no violence, pornography or sara in the Game “Endless Runner”. This game can be played when you have free time and anywhere because the Game “Endless Runner” is made for Android. Learning tools using the Game “Endless unner” helps children love math lessons